PENYULUHAN SEPTICTANK DENGAN BIDANG RESAPAN PEKON GISTING PERMAI KABUPATEN TANGGAMUS PROVINSI LAMPUNG - Oktarina, Devi; Febrina, Rina; Rudiansyah, Rudiansyah; Erlangga, Deni; Habsyi, M Alfi Al; Otimah, Otimah; Mulyado, Riski; Celvin, Raid; Rendi, Ketut (Jurnal Bakti Masyarakat Manajemen, 2024)
Poor sanitation is a serious problem that still occurs, especially in areas that do not yet have an independent waste management system. This condition has a significant impact on public health, especially increasing the risk of environmental diseases such as diarrhea, cholera, and typhus. In addition, inadequate sanitation can also pollute clean water sources and soil, damage ecosystems, and reduce the quality of life of the community as a whole. Pekon Gisting Permai as one of the areas in Tanggamus Regency, Lampung Province which is currently developing, also faces challenges in terms of sanitation. Many houses do not yet have proper sanitation facilities such as septic tanks, so that human waste (feces and urine) is disposed of carelessly in the surrounding environment. This not only causes an unpleasant odor, but also becomes a potential source of the spread of disease. A simple septic tank is present as an appropriate and affordable sanitation solution for the community. By utilizing the natural process of waste processing by microorganisms and absorption systems, a simple septic tank is able to reduce the burden of environmental pollution and protect clean water sources. In addition, simple septic tanks are easy to build and maintain, making them suitable for use in areas with limited resources. However, many people still do not understand the importance of good sanitation and the benefits of simple septic tanks. Lack of knowledge about how to build, operate, and maintain simple septic tanks is also an obstacle to their implementation.